Structural insights into modulation and selectivity of transsynaptic neurexin–LRRTM interaction - Atsushi Yamagata (Nature Portfolio, 2018)
Leucine-rich repeat transmembrane neuronal proteins (LRRTMs) function as postsynaptic organizers that induce excitatory synapses. Here authors solve the crystal structure of LRRTM2 in complex with its ligand Nrxn1β and shed light on how selective binding of ligands to LRRTM1/2 is achieved.